Sos1 Modulates Extracellular Matrix Synthesis, Proliferation, and Migration in Fibroblasts - Fuentes-Calvo, Isabel; Martinez-Salgado, Carlos (Frontiers in Physiology, 2021)
Non-reversible fibrosis is common in various diseases such as chronic renal failure, liver cirrhosis, chronic pancreatitis, pulmonary fibrosis, rheumatoid arthritis and atherosclerosis. Transforming growth factor beta 1 (TGF-β1) is involved in virtually all types of fibrosis. We previously described the involvement of Ras GTPase isoforms in the regulation of TGF-β1-induced fibrosis. The guanine nucleotide exchange factor Son of Sevenless (Sos) is the main Ras activator, but the role of the ubiquitously expressed Sos1 in the development of fibrosis has not been studied. For this purpose, we isolated and cultured Sos1 knock-out (KO) mouse embryonic fibroblasts, the main extracellular matrix proteins (ECM)-producing cells, and we analysed ECM synthesis, cell proliferation and migration in the absence of Sos1, as well as the role of the main Sos1-Ras effectors, Erk1/2 and Akt, in these processes. The absence of Sos1 increases collagen I expression (through the PI3K-Akt signalling pathway), total collagen proteins, and slightly increases fibronectin expression; Sos1 regulates fibroblast proliferation through both PI3K-Akt and Raf-Erk pathways, and Sos1-PI3K-Akt signalling regulates fibroblast migration. These study shows that Sos1 regulates ECM synthesis and migration (through Ras-PI3K-Akt) and proliferation (through Ras-PI3K-Akt and Ras-Raf-Erk) in fibroblasts, and describe for the first time the role of the Sos1-Ras signalling axis in the regulation of cellular processes involved in the development of fibrosis.